2000
DOI: 10.1111/1468-2354.00062
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Speed of Transition: A General Equilibrium Analysis

Abstract: We present a benchmark model for the optimal speed of transition from a state-owned to a private market economy, based on the consumption-savings decision in a closed economy. We abstract from frictions to focus on the macroeconomic conditions for accumulation of private capital and closure or restructuring of state-owned enterprises. It is shown that hard budget constraints compensate for too slow speed of enterprise closure but that an excess speed of closure may slow down transition because of output contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 18 publications
1
54
1
Order By: Relevance
“…Of course, the interpretation of this finding must be careful: for instance, whenever the transition process involves a peak in the rate of unemployment, the size of the economy may actually shrink before enlarging so that our results could be initially reversed (Castanheira and Roland, 1996;Coricelli, 1998). Thus, simultaneous exclusion from the integration process and ongoing transition have unpredictable effects on the structural adjustment, which might even exhibit a swinging behavior.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Of course, the interpretation of this finding must be careful: for instance, whenever the transition process involves a peak in the rate of unemployment, the size of the economy may actually shrink before enlarging so that our results could be initially reversed (Castanheira and Roland, 1996;Coricelli, 1998). Thus, simultaneous exclusion from the integration process and ongoing transition have unpredictable effects on the structural adjustment, which might even exhibit a swinging behavior.…”
Section: Discussionmentioning
confidence: 95%
“…A 'transition economy' (TE) is defined as an economy where poor enforcement of property rights, high administrative and bureaucratic costs, and widespread corruption abate average labor productivity; the 'transition process' involves the removal of these obstacles to the rise of labor productivity. This definition builds on the traditional modelling of transition as a process of resource reallocation from state-owned to private enterprises (see, among others, Castanheira and Roland, 1996;and Coricelli, 1998, chapter 3) while it departs from Halpern and Wyplosz (1997, p.438-39) who suggest that, due to poor quality and marketing, domestically produced tradables are sold at a discount on world markets. More specifically we assume that, because of inefficiencies and rent-seeking activities, unit labor productivity is proportionally smaller in TEs relative to market economies in both productive sectors.…”
Section: Location and Terms-of-trade Effects Of Economic "Transition"mentioning
confidence: 99%
See 1 more Smart Citation
“…Models of transition from plan to market assume that the turnover (inflow) rate would rise dramatically as the old state sector sheds workers who go through unemployment into new jobs that are being created in the emerging private sector (e.g., Aghion and Blanchard, 1994, Blanchard, 1997, and Castanheira and Roland, 2000. The models predict that the inflow rate would be temporarily very high and gradually decline and approach the level observed in otherwise similar market economies such as West Germany.…”
Section: The Role Of Labor Turnover In Economic Adjustmentsmentioning
confidence: 99%
“…On the aggregate level, the labor relocation from the less productive state to the more productive private sector was a key issue in the theoretical literature, pioneered by Aghion and Blanchard (1994), and further developed by Atkinson and Kehoe (1996) and Brixiova and Kiyotaki (1997), Castanheira and Roland (2000) and others. The experience of the past two decades has shown that a successful transition hinges on the dynamic private sector, and especially new firms, to drive the productivity and employment growth.…”
Section: Introductionmentioning
confidence: 99%